Age Distribution of Multiple Functionally Relevant Subsets of CD4+ T Cells in Human Blood Using a Standardized and Validated 14-Color EuroFlow Immune Monitoring Tube - Botafogo, Vitor; Pérez-Andres, Martín; Jara-Acevedo, María; Bárcena, Paloma; Grigore, Georgiana; Hernández-Delgado, Alejandro; Damasceno, Daniela; Comans, Suzanne; Blanco, Elena; Romero, Alfonso; Arriba-Méndez, Sonia; Gastaca-Abasolo, Irene; et al. (Frontiers in Immunology, 2020)
CD4+ T-cells comprise multiple functionally distinct cell populations that play a key role in immunity. Despite blood monitoring of CD4+ T-cell subsets is of potential clinical utility, no standardized and validated approaches have been proposed so far. The aim of this study was to design and validate a single 14-color antibody combination for sensitive and reproducible flow-cytometry monitoring of CD4+ T-cell populations in human blood to establish normal age-related reference values and evaluate the presence of potentially altered profiles in three distinct disease models -monoclonal B-cell lymphocytosis (MBL), systemic mastocytosis (SM) and common variable immunodeficiency (CVID). Overall, 130 blood samples from healthy donors were used to design and validate a 14-color antibody combination based on extensive reagent testing in multiple cycles of design-testing-evaluation-redesign, combined with in vitro functional studies, gene expression profiling and multicentric evaluation of manual vs automated gating. Fifteen cord blood and 98 blood samples from healthy donors (aged 0-89y) were used to establish reference values and another 25 blood samples were evaluated for detecting potentially altered CD4 T-cell subset profiles in MBL (n=8), SM (n=7) and CVID (n=10). The 14-color tube can identify ≥89 different CD4+ T-cell populations in blood, as validated with high multicenter reproducibility, particularly when software-guided automated (vs. manual expert-based) gating was used. Furthermore, age-related reference values were established, which reflect different kinetics for distinct subsets: progressive increase of naïve T-cells, Th1, Th17, TFH and Tregs from birth until 2y, followed by a decrease of naïve, Th2 and Tregs in older children and a subsequent increase in multiple Th-cell subsets toward late adulthood. Altered and unique CD4+ T-cell subset profiles were detected in two of the three disease models evaluated (SM and CVID). In summary, the EuroFlow immune monitoring TCD4-tube allows fast, automated and reproducible identification of ≥89 subsets of CD4+ blood T-cells, with different kinetics throughout life. These results set the basis for in-depth T-cell monitoring in different disease and therapeutic conditions.